The economics of cowpea in West Africa - Coulibaly, O.; Lowenberg-Deboer, J. (2002)
The contribution of cowpea to food security and poverty reduction can be substantial in West Africa if both biological and socioeconomic constraints are addressed. While some attention has been given to genetics, agronomy, and pest control, such economic issues as access to input, marketing, and consumer preferences are key research areas which contribute to the adoption and wide diffusion of improved cowpea technologies among small farmers. An area neglected in cowpea research but which is becoming important is consumer appreciation of improved cowpea grain. Results from the hedonic pricing analysis showed, for example, that consumers prefer larger grain size and seeds with low level of bruchid damage. Another area which needs to be investigated is the financial and economic profitability of chemical-intensive cowpea technologies. Cowpea is very sensitive to pests and chemical protection of the crop is financially profitable. However, this financial profitability may substantially decrease if hidden costs, such as the opportunity costs of capital, health hazards, and environmental costs are taken into consideration. This calls for the adoption of more environmentally sound and health con scious crop protection techniques such as the use of botanicals and an integrated pest management approach for cowpea research. The study also reviews the economic impact of cowpea research and concludes that the integration of biological and social science in cowpea research will lead to sustainable technology development for food security and poverty reduction.